The status of cattle genetic resources in North Ethiopi: On-farm charcterization of six major cattle breeds - Zerabruk, M; Vangen, O.; Haile, M. (2007)
On-farm surveys and characterization of six indigenous north Ethiopian cattle breeds (Afar, Arado, Begait, Fogera, Medenes and Raya) was carried out with the objective of determining the current status of these breeds. Information from a structured questionnaire distributed to 450 farmers, 37 group discussions, field measurements of heart girth and height on 25 males and 25 females from each breed and secondary information were used to carry out the study. Population size of Arado breed increased by more than three fold between 1992 and 1999, while the Raya, Fogera and Begait population decreased by 57, 27 and 67%; between 1981 and 1999 respectively. Three distinctive types were identified within the Afar and Begait breeds with different adaptation and threat levels in relation to changes to the bio-physical and social environment. Overall production and reproduction performance of the breeds in the pastoral production system (Afar and Arado and Fogera breeds of the agro-pastoral and mixed crop/ livestock production systems respectively. Extinction probability for most of the breeds was high, the highest (0.67) being for the Begait breed. On the other hand, except for the initiative taken to evaluate, improve and conserve the Fogera breed at the Metekel and Andasa cattle breedin ranches, there are no institutionalized attempts towards improving and/ or conserving the other breeds.